Pattern Variation Method to Detect Lie Using Artificial Neural Network (PVMANN) - Chakraborty, Shantanu; Mandal, Rakesh Kumar (International Journal of Computer Sciences and Engineering, 2025)
This beautiful world is a collection of variety of people. They have different sort of mind. Some people always speak the truth. Some hardly have the habits to tell the truth. If a person is guilty then he or she must try to save him or herself and conceal his or her sin. If a system can be designed to detect lie then a genuine and trusty counseling can be done for the establishment of the truth. This paper contains an algorithm PVMANN which makes a gateway to detect a person’s truthfulness.